Cassius Dio's Speeches and the Collapse of the Roman Republic : The Roman History, Books 3-56 - Burden-Strevens, Christopher, (Historiography of Rome and Its Empire ;, 2020)
In Cassius Dio's Speeches and the Collapse of the Roman Republic, Christopher Burden-Strevens provides a radical reinterpretation of the importance of public speech in one of our most significant historical sources for the bloody and dramatic transition from Republic to Principate. Cassius Dio's Roman History, composed in eighty books early in the 3rd century CE, has only recently come to be appreciated as a sophisticated work of history-writing. In this book, Burden-Strevens demonstrates the central role played by speeches in Dio's original analysis of the decline of the Republic and the success of the emperor Augustus' regime, including a detailed study of their possible sources, themes, methods of composition, and their distinctiveness within the traditions of Roman historiography.